Primary and recurrent glaucoma-induced disability in senior working-age population in the Altai territory - S. I. Makogon; A. S. Makogon (Российский офтальмологический журнал, 2018)
Purpose: To study primary and recurrent glaucoma-induced disability in senior working-age people in the Altai Territory over the period of 2004-2013. Material and methods. The data of the Bureau of medico-social examination for the period have been analyzed to determine the main parameters of disability: the intensive (primary disability prevalence per 10 thousand individuals) and the extensive markers (percentage distribution of primary disability causes). Results. Over the researched period, the number of Altai territory individuals registered as invalids for the first time due to diseases of the eye and adnexa decreased by 2.14 times, while the number of people classified as recurrent invalids showed a 1.4 - fold increase. In the nosological structure of primary disability due to diseases of the eye and adnexa, glaucoma consistently claimed rank 1, while in recurrent disability glaucoma rose from rank 3 to rank 1, and its share in the structure of repeated disability causes increased by 2.1 times. The cohort of primary and recurrent glaucoma-induced invalids mainly includes people older than the official working age, who claimed 87.4 % and 61.6 % in primary and recurrent disability, respectively. The proportion of invalids of group I (41.3 and 40.2 %) and group II (37.7 and 38.2 %), respectively for primary and recurrent disability, was significantly higher than the proportion of III group invalids (21 and 21.6 %, respectively). Conclusion. The dynamics and structure of primary and recurrent glaucoma-induced disability in senior working-age population showed that the tactics of prevention, concrete preventive measures, and rehabilitation procedures for glaucoma patients need to be developed. For citations: Makogon S.I., Makogon A.S. Primary and recurrent glaucoma-induced disability in senior workingage population in the Altai territory. Russian ophthalmological journal. 2017; 10 (3): 42-48. doi: 10.21516/2072-0076-2017-10-3-42-48 (in Russian).